Daya Tarik Tambang untuk Pemenuhan Kebutuhan Petani di Desa Morosi Kecamatan Morosi Kabupaten Konawe - Lilis, Lilis; Nalefo, La; Arimbawa, Putu (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2017)
This study aims to determine the attractiveness of mines in meeting the social and economic needs of people in Morosi Village Morosi Sub-District Konawe. The study was conducted from March to June 2017. The results show that: 1) the low economic literacy impact on welfare, therefore the priority to increase economic literacy becomes a necessity for individuals or families who want to prosper. In other words, increasing the mastery of economic literacy is inexorable but a necessity and it can be initiated from a continuous learning passion. Considering that the increase in specific economic literacy has a positive impact on asset accumulation, deaccumulation of debt, protection, accumulation of saving and the carefulness of managing expenditure. Working on the mine with sufficient monthly data collection can be an increase in knowledge and economic literacy. 2) Socially with mined work will be fulfilled all. Needs to help families especially in weddings, art needs and so on.